Evolution of Retrograde Transvenous Obliteration Techniques - Patel, Mihir; Molvar, Christopher (Seminars in Interventional Radiology, 2018)
Gastric variceal hemorrhage is a life-threatening complication of portal hypertension with a poorer prognosis compared with esophageal variceal hemorrhage. The presence of an infradiaphragmatic portosystemic shunt, often a gastrorenal shunt, allows for treatment with retrograde transvenous obliteration (RTO). RTO is an evolving treatment strategy, which includes balloon-assisted RTO, plug-assisted RTO, and coil-assisted RTO, for both gastric variceal hemorrhage and hepatic encephalopathy. RTO techniques are less invasive than transjugular intrahepatic portosystemic shunt creation, with the benefit of improved hepatic function, but at the expense of increased portal pressure. This article discusses the techniques of RTO, including patient eligibility, as well as technical and clinical outcomes, including adverse events.
Keywords: retrograde transvenous obliteration; varices; portal hypertension; cirrhosis; hemorrhage